Grafting Area Reduction in Peyronie's Disease Surgery: Comparative Assessment Between Double Y Vs iGrafter APP Using 3D-Printed Penile Models. Issue 4 (23rd February 2022) - Tourchi, Ali; Nascimento, Bruno; de Freitas Miranda, Alexandre; Miranda, Eduardo; Bessa, José; Nahas, William C.; Filho, Rogério Sayão; Srougi, Miguel; Machado, Bruno
ABSTRACT: Background: The use of plaque incision and graft techniques (PIG) for the treatment of severe Peyronie's disease (PD), may lead to erectile dysfunction (ED); graft size is 1 of the contributing factors for post-PIG ED. Recently the iGrafter software APP was introduced using a mathematical algorithm to distribute the incisions along the penile length resulting in a smaller grafting area. Aim: Compare 2 PIG techniques, the Double-Y(DY) and iGrafter, in 3 main aspects: (i) Total grafting area; (ii) The variation in calculating the grafting to be used; (iii) time to perform the PIG. Methods: Six urologists with expertise in sexual medicine performed both techniques twice using four 3-D validated training models for PD with a standard 60° uniplanar dorsal curvature. Outcomes: The graft areas and operative partial and total time for each step of the operation were recorded for each procedure. Unpaired t -test and the coefficient of variation for graft area across surgeons was calculated comparing both techniques. Results: For all surgeons, the use of iGrafter resulted in 2 grafts, for the DY technique in 1 graft. Overall, TT for the iGrafter was significantly longer than for DY technique (49.4 ± 11 vs 40.7 ± 5.7 minute; P = .02), The iGrafter grafting area was significantly smaller (11.6 ± 1.2 vs 23.3 ± 5.4 cm 2 ; P : .01), representing a 50.2% area reduction when compared to the DY. The variation of graft area, using the iGrafter also yielded a more consistent graft across all surgeons (CV = 10.56% vs 23.28%). Clinical Significance: The iGrafter, when compared to DY technique, reduced the graft area by 50%, which potentially means less erectile dysfunction. Strengths and Limitations: Our study eliminates anatomical variations found in a real clinical case making it possible to compare surgical techniques with the same penile anatomy. However, the 3D-printed model cannot replicate the living human tissue property preventing a simulation close to actual surgery. Conclusion: The use of the iGrafter software for PIG surgery has shown to be a promising technique for severe PD management resulting in smaller graft size (about 50% smaller when compared to the DY), although it might be more time-consuming.